"Etude de l’effet de l’ajout de granulats de caoutchouc recyclés de pneus usagés sur le comportement de mortier de ciment." - عمار, خلايفة; الفضل, عرفة; شرف, ربيعات (University of El-Oued, 2021)
"The cementing materials are handicapped by their low tensile strength and their brittleness, which make them particularly sensitive to cracking in particular the cracking of withdrawal. If brittleness is often mitigated by the reinforcement by reinforcements, their installation is difficult even impossible in certain cases. The reinforcement by fibers is an alternative solution which remains perfectible in this direction where this one does not prevent cracking but in limit the opening. The ideal solution is a cementing material able to support important deformations before localization of the fissure. This objective, we chose the incorporation of deformable aggregates in substitution of the sand and we decided to use rubber aggregates resulting from the crushing of worn tires. These aggregates were introduced in voluminal substitution partial of the natural aggregates. In the other hand falls of resistances in compression and traction, the capacity of deformation before localization of the macro cracking is definitely higher in the presence of aggregates rubber. The results showed that the composite obtained with a greater resistance to the cracking of withdrawal. Thus, when resistance to cracking is a priority, the incorporation of aggregates rubber in cementing materials is an answer for more durable applications and constitutes a new way of valorization of the no reusable worn tires. " "المواد الإسمنتية معطلة بسبب قوتها للشد منخفضة وهشاشتها ، مما يجعلها حساسة بشكل خاص للتشقق ، ولا سيما الانكماش. إذا تم التغلب على الهشاشة غالبًا عن طريق التعزيزات ، يكون تركيبها صعبًا أو مستحيلًا في بعض الحالات. يعد التعزيز بالألياف حلاً بديلاً لا يزال من الممكن تحسينه بمعنى أنه لا يمنع التشقق ولكنه يحد من فتحه. الحل المثالي هو اقتراح مادة اسمنتية قادرة على تحمل التشوهات الكبيرة قبل تحديد موقع التشقق. لهذا الغرض ، اخترنا دمج الركام القابل للتشوه كبديل للرمل وقررنا استخدام ركام المطاط من تمزيق الإطارات المستعملة كبديل جزئي للحجم للركام الطبيعي. في مقابل الانخفاضات في مقاومة الانضغاط والشد ، تكون قدرة التشوه قبل توطين التشققات أعلى بشكل ملحوظ في وجود مجاميع المطاط. أظهرت النتائج أن المركب الناتج لديه مقاومة أكبر للتشقق. وبالتالي ، عندما تكون مقاومة التشقق أولوية ، فإن دمج ركام المطاط في المواد الإسمنتية يمثل استجابة لتطبيقات أكثر متانة ويشكل طريقة جديدة لتثمين الإطارات المستعملة الغير القابلة لإعادة الاستخدام. "
Matéreaux en génie civil مذكرة ماستر تخصص
Keywords: Keywords: Scrap rubber, cementing composite, Mortar, properties physic mechanical, cementing Materials, rubber Aggregates, Capacity of deformation, Recycling.; كلمات البحث : حبيبات المطاط ، الملاط ، الخصائص الفيزيائية و الميكانيكية ، المواد الاسمنتية ، متانة.